1990
DOI: 10.1002/ana.410270612
|View full text |Cite
|
Sign up to set email alerts
|

Mania after brain injury: Neuroradiological and metabolic findings

Abstract: We present a consecutive series of 8 patients who developed a manic episode after a brain injury. Five patients had cortical lesions (4 with damage to the right basotemporal region, and 1 with bilateral damage to the orbitofrontal area). While the other 3 patients had subcortical lesions (white matter of the right frontal lobe, right anterior limb of the internal capsule, and right head of the caudate), a fluorodeoxyglucose positron emission tomography scan showed hypometabolism in the right lateral basotempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(69 citation statements)
references
References 15 publications
7
58
0
4
Order By: Relevance
“…The majority of the studies were case reports (71%) [7,8,17,19,20,21,22,23,24,25,27,28,29,30,32,33,34,35,36,37,38,39,40,41,43,44,45,46,47,48,49,56,57,58,60], followed by case series (14%) [16,18,26,31,51,53,54] and cohort studies (8%) [12,42,52,61]. The fact that case reports are usually shorter descriptions explains the lack of information we found when we tried to assess other parameters of the diagnosis and assessment.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were case reports (71%) [7,8,17,19,20,21,22,23,24,25,27,28,29,30,32,33,34,35,36,37,38,39,40,41,43,44,45,46,47,48,49,56,57,58,60], followed by case series (14%) [16,18,26,31,51,53,54] and cohort studies (8%) [12,42,52,61]. The fact that case reports are usually shorter descriptions explains the lack of information we found when we tried to assess other parameters of the diagnosis and assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In one study the prevalence [4] of postinfarct depression varied from 25% to 50% during the recuperation phase and in another [5] between 18% and 78% in the first two years, reaching its highest point between 3 and 6 months after stroke. Other authors [6,7] observed hypomanic episodes in patients with thalamic lesions of vascular origin in the right hemisphere. Starkstein et al [8] suggested that lesions in the basotemporal lobe and orbitofrontal cortical region lead to a syndrome of disinhibition, secondary to a manic process.…”
Section: Introductionmentioning
confidence: 90%
“…A maior parte dos relatos associa-se a lesões no hemisfério direito, incluindo lobos frontais ou temporais, tálamo ou núcleo caudado. Nesse sentido, Starkstein et al 94 observaram hipometabolismo da região temporal inferior direita em três pacientes com mania associada a lesões subcorticais. Os autores sugerem, como mecanismo fisiopatológico, disfunção da alça fronto-estriado-tálamo-cortical interconectada ao sistema límbico e ao lobo temporal, principalmente o direito.…”
Section: Maniaunclassified